2016
DOI: 10.1038/srep23799
|View full text |Cite
|
Sign up to set email alerts
|

Dcc Mediates Functional Assembly of Peripheral Auditory Circuits

Abstract: Proper structural organization of spiral ganglion (SG) innervation is crucial for normal hearing function. However, molecular mechanisms underlying the developmental formation of this precise organization remain not well understood. Here, we report in the developing mouse cochlea that deleted in colorectal cancer (Dcc) contributes to the proper organization of spiral ganglion neurons (SGNs) within the Rosenthal’s canal and of SGN projections toward both the peripheral and central auditory targets. In Dcc mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
1
9
1
Order By: Relevance
“…Our results contrast with those from previous studies that reported no phenotypes in the spiral ganglion of Ntn1 hypomorphs ( Howell et al, 2007 ; Kim et al, 2016 ). These differences could be attributed to the hypomorphic nature of the Ntn1 trap/trap mice, which show a weaker phenotype: many PNs get close to their final destination ( Figures S4D and S4D’ ), and there are significantly fewer Pax6+ cells in E15.5 Ntn1 trap/trap cochleae ( Figures S4B–S4C’ ; n = 6 cochleae).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results contrast with those from previous studies that reported no phenotypes in the spiral ganglion of Ntn1 hypomorphs ( Howell et al, 2007 ; Kim et al, 2016 ). These differences could be attributed to the hypomorphic nature of the Ntn1 trap/trap mice, which show a weaker phenotype: many PNs get close to their final destination ( Figures S4D and S4D’ ), and there are significantly fewer Pax6+ cells in E15.5 Ntn1 trap/trap cochleae ( Figures S4B–S4C’ ; n = 6 cochleae).…”
Section: Resultscontrasting
confidence: 99%
“…More recently, several groups have demonstrated that commissural guidance depends on ventricular- zone-derived Ntn1 accumulating in the SPR and along the commissural axons ( Dominici et al, 2017 ; Varadarajan et al, 2017 ; Yamauchi et al, 2017 ), expanding on related observations ( Charron et al, 2003 ; Kennedy et al, 2006 ). We have similarly revealed a role for SPR-localized Ntn1 in cellular confinement, providing an alternative explanation for both the reduced number of PNs in Ntn1 trap/trap mice, which was thought to reflect Ntn1’s tropic and trophic roles ( Yee et al, 1999 ), and the presence of ectopic neurons in DCC −/− cochleae, which was attributed to a mis-positioning of SGNs ( Kim et al, 2016 ). Thus, across multiple species and in multiple regions of the nervous system, Ntn1 appears to act locally to mediate its purported long-range functions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Typically, during axon guidance, navigating growth cones interpret guidance cues in the environment through cell-surface receptors that initiate cell-signaling cascades and dynamic changes in the cytoskeleton (Bashaw and Klein, 2010;O'Donnell et al, 2009). The role of classic axon guidance cues, including semaphorin, ephrin, slit and netrin, and the neurotrophic factors neurotrophin 3 and brain-derived neurotrophic factor have been studied extensively during SGN development and patterning in the mouse (Coate et al, 2015;Defourny et al, 2013;Fritzsch et al, 1997a,b;Kim et al, 2016;Wang et al, 2013). Although these molecules make important contributions to SGN survival and migration, and towards the patterning of type I SGNs, type II SGN axon turning is not altered when the genes encoding these proteins are mutated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, misplaced SGNs in the modiolus are in Ntrk2 and Ntrk3 neurotrophin receptor mutants 37 . Less severe phenotypes of misplaced SGNs have been reported for mice lacking Dcc 41 or mice with deficient Slit/Robo signaling 40 . All these reported SGN migration defects are also associated with abnormalities in projections.…”
Section: Discussionmentioning
confidence: 86%